Relational Incentive Contracts with Persistent Private Information - James Malcomson (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper investigates relational incentive contracts with continuous, privately-observed agent types that are persistent over time. With fixed agent types, full separation is not possible when continuation equilibrium payoffs following revelation are on the Pareto frontier of attainable payoffs. This result is related to the ratchet effect in that: (1) a type imitating a less productive type receives an information rent and (2) with full separation, one imitating a more productive type receives the same future payoff as that more productive type. However, the reason for (2) is fundamentally different than with the ratchet effect. It arises from the dynamic enforcement requirement in relational contracts, not from the principal having all the bargaining power, and applies whatever the distribution between principal and agent of the future gains from the relationship (that is, whatever the point on the Pareto frontier). This result extends to sufficiently persistent types under certain conditions.
Keywords: C73; D82; D86; 330; relational incentive contracts; private information; ratchet effect; dynamic enforcement